−0.9−3.3y=




13.77
−13.77

1 answer

There are two possible ways to evaluate this expression, depending on whether it is asking for a numerical answer or for simplification:

- Numerical answer:

To find the value of the expression when y is substituted by a specific number, such as y = 2, we can simply plug in this value and calculate:

-0.9 - 3.3(2) = -7.5

Therefore, -0.9 - 3.3y is equal to -7.5 when y equals 2.

- Simplification:

To simplify the expression as much as possible, we can use the distributive property of multiplication over subtraction, which states that a(b - c) = ab - ac. Applying this rule, we get:

-0.9 - 3.3y = (-0.9) - (3.3y)
= (-0.9) - (3.3)(y)
= -0.9 - 3.3y

This means that the expression cannot be simplified any further, and its value depends on the value of y.